Participation in competitive employment after severe traumatic brain injury: New employment versus return to previous (pre-injury) employment. Issue 6 (2nd July 2020) - Simpson, Grahame K.; McRae, Philippa; Hallab, Lisa; Daher, Maysaa; Strettles, Barbara
ABSTRACT: There is limited literature comparing the clinical and employment characteristics of clients accessing new employment with those resuming previous employment. To address this gap, a multi-centre observational study was conducted of all active clients with severe TBI from the 11 community rehabilitation services ( n = 588) of the New South Wales Brain Injury Rehabilitation Program. Demographic, injury, clinical and vocational data were collected by treating clinicians employing a purpose-designed protocol. New employment constituted almost 40% of competitive employment outcomes. Clients accessing new employment were significantly more likely to be younger, single, less educated, with more severe injuries and more likely to be displaying challenging behaviours than those resuming pre-injury work. Kaplan-Meier analyses found time to RTW was significantly longer for new employment. Stability of new employment was significantly poorer with jobs twice as likely to break down compared to previous employment. New employment positions were also more likely to be part-time and unskilled compared to previous employment. The results found that placement into new employment made a substantial contribution to employment outcomes after TBI but requires more intensive and tailored programmes to meet the multiple clinical and workplace challenges.